Wikipedia and the Representation of Reality - McDowell, Zachary J. (Taylor & Francis, 2022)
A contemporary examination of what information is represented, how that information is presented, and who gets to participate (and serve as gatekeeper) in the world's largest online repository for information, Wikipedia. Bridging contemporary education research that addresses the 'experiential epistemology' of learning to use Wikipedia with an understanding of how the inception and design of the platform assists this, the book explores the complex disconnect between the encyclopedia's formalized policy and the often unspoken norms that govern its knowledge-making processes. At times both laudatory and critical, this book illustrates Wikipedia's struggle to combat systemic biases and lack of representation of marginalized topics as it becomes the standard bearer for equitable and accessible representation of reality in an age of digital disinformation and fake news. Being an important and timely contribution to the field of media and communication studies, this book will appeal to academics and researchers interested in digital disinformation, information literacy, and representation on the Internet, as well as students studying these topics.